2008
DOI: 10.1055/s-2008-1044632
|View full text |Cite
|
Sign up to set email alerts
|

Zur operativen Behandlung der schnappenden Hüfte

Abstract: Snapping hip (Coxa saltans) is the abrupt sliding of the iliotibial tract over the greater trochanter. In the case of pain, which cannot be alleviated by a conservative treatment, an operation is advised. The methods of operation applied up to this day showed--especially because of their high recidive-quotas--great disadvantages. In a detailed post-operational check-up over the past 20 years the new method of "diagonal notching" (27 cases) developed at the Orthopedic Hospital München-Harlaching was compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is likely that incomplete removal of the bursa or other pathologies may be responsible for this residual pain. Other authors have reported incomplete pain resolution in their series (3,14,18,32,33) but the causes are poorly understood. Further investigation is needed to clarify the origin of this complaint.…”
Section: Zini Et Almentioning
confidence: 87%
“…It is likely that incomplete removal of the bursa or other pathologies may be responsible for this residual pain. Other authors have reported incomplete pain resolution in their series (3,14,18,32,33) but the causes are poorly understood. Further investigation is needed to clarify the origin of this complaint.…”
Section: Zini Et Almentioning
confidence: 87%